2013
DOI: 10.1590/s2179-83972013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Implante por cateter de bioprótese valvular aórtica para tratamento de estenose valvar aórtica grave em pacientes inoperáveis sob perspectiva da saúde suplementar: análise de custo-efetividade

Abstract: Background: Transcatheter aortic valve implantation (TAVI) is a new modality of treatment especially dedicated to patients with high surgical risk. In these patients, TAVI increased survival and improved quality of life when compared to standard treatment (drug therapy with or without percutaneous aortic balloon valvuloplasty). Our objective was to perform a costefficacy analysis of the implementation of TAVI in the Brazilian Supplemental Health System. Methods: We developed a predictive model to assess the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
4
0
5
Order By: Relevance
“…(11) In this study, our results matched several case studies published, in which we could notice a a similar profile. (2,3,11,14) The main pre-implant comorbidities presented by the patients were hypertension, dyslipidemia, high body mass index, non-dialysis chronic kidney disease, heart failure, diabetes mellitus, and current or former smokers. In previous studies, similar data were already found, highlighting the coronary artery disease, peripheral artery disease, prior cerebrovascular accident and prior coronary artery bypass grafting (CABG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) In this study, our results matched several case studies published, in which we could notice a a similar profile. (2,3,11,14) The main pre-implant comorbidities presented by the patients were hypertension, dyslipidemia, high body mass index, non-dialysis chronic kidney disease, heart failure, diabetes mellitus, and current or former smokers. In previous studies, similar data were already found, highlighting the coronary artery disease, peripheral artery disease, prior cerebrovascular accident and prior coronary artery bypass grafting (CABG).…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, the high percentage of systemic arterial hypertension and heart failure were extremely relevant. (3,9,11,14) In the PARTNER study, the profile found was as follows: women (57.8%), elderly people (83.6 ± 6.8) with comorbidities such as New York Heart Association (NYHA) class III or IV (94.3%), coronary artery disease (74.9%), chronic obstructive pulmonary disease (DPOC) (52.6%), peripheral vascular disease (43%), prior coronary artery bypass grafting surgery (42.6%), pulmonary hypertension (42.4%), atrial fibrillation (40.8%), previous angioplasty (34%), cerebrovascular accident (29.3%), previous acute myocardial infarction (26.8%), and definitive pacemaker (20%).…”
Section: Resultsmentioning
confidence: 99%
“…In the present issue of Revista Brasileira de Cardiologia Invasiva, Queiroga et al 20 evaluate, in a detailed study from the perspective of the private healthcare system, the ICER of TAVR in Brazil. Using estimates of the direct medical costs of the procedure (regarding hospital admission, the procedure itself, and administered medications) and the predictive statistical model based on the results of the PARTNER B trial, the authors performed an economic analysis of TAVR on the national scene.…”
Section: Would Tavr Be a Treatment Of Appropriate Economic Value?mentioning
confidence: 99%
“…The inclusion of the costs of aortic valvuloplasty in the group of patients kept under strict medical treatment could result in even lower values of ICER in the economic model adopted. Finally, it should be noted that the conclusions of the article of Queiroga et al 20 are based on the results of inoperable patients undergoing TAVR, and should not be extrapolated to patients with high surgical risk (assessed in the PARTNER A trial, with specific analysis of cost-effectiveness). 21 Ultimately, the challenge remains: how assure to the patients the high clinical value effectiveness of TAVR reconciling them to their high cost economic in Brazil?…”
Section: Would Tavr Be a Treatment Of Appropriate Economic Value?mentioning
confidence: 99%
“…Por ser de grande valia na tomada de decisões, facilita na escolha mais adequada, focando sempre a relação custo/efetividade dos procedimentos, considerando como resultado esperado a melhora da condição de saúde do paciente 49,67,119,121,129 . • Em razão da homogeneidade das características demográficas e clínicas dos pacientes, estas não foram consideradas fatores preditores para o aumento no custo médio do procedimento TAVI.…”
Section: Discussão Dos Resultados 133unclassified